The Novel Formation of Barium Titanate Nanodendrites. (30th April 2014) - Huang, Chien-Jung; Chen, Kan-Lin; Chiu, Pin-Hsiang; Sze, Po-Wen; Wang, Yeong-Her
Abstract : The barium titanate (BaTiO3 ) nanoparticles with novel dendrite-like structures have been successfully fabricated via a simple coprecipitation method, the so-called BaTiO3 nanodendrites (BTNDs). This method was remarkable, fast, simple, and scalable. The growth solution is prepared by barium chloride (BaCl2 ), titanium tetrachloride (TiCl4 ), and oxalic acid. The shape and size of BaTiO3 depend on the amount of added BaCl2 solvent. To investigate the influence of amount of BaCl2 on BTNDs, the amount of BaCl2 was varied in the range from 3 to 6 mL. The role of BaCl2 is found to have remarkable influence on the morphology, crystallite size, and formation of dendrite-like structures. The thickness and length of the central stem of BTND were 300 nm and 20 μ m, respectively. The branchings were found to occur at irregular intervals along the main stem. Besides, the formation mechanism of BTND is proposed and discussed.